Studi Kualitatif tentang Persepsi Masyarakat Muda terhadap Isu Politik di Media Sosial pada Pilpres 2024 - Ummanah Ummanah; Yoseph Hari Pramono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to understand the perceptions of young voters towards political issues that develop on social media during the 2024 Presidential Election (Pilpres). This study uses a case study design method. The sampling technique is purposive sampling, namely selecting 30-40 participants who meet the criteria. The results of the study show that social media plays an important role as a political discussion space for the younger generation. Young voters are not only consumers of political information, but also actively produce and disseminate content that forms certain political narratives. However, their involvement is also overshadowed by opinion polarization, echo chambers, and low digital and political literacy. The conclusions from these findings support the theories of uses and gratifications, public sphere, and social identity, and indicate that social media not only shapes political perceptions, but also the political identity of the younger generation digitally. Keywords: Political Issues, Social Media, Young People's Perceptions, 2024 Presidential Election.